Advances in Ergonomic Design of Systems, Products and Processes: Proceedings of the Annual Meeting of GfA 2015 - Deml, Barbara; Stock, Patricia Isabel; Bruder, Ralph; Schlick, Christopher (SpringerLink Bücher, 2016)
These proceedings summarize the best papers in each research area represented at the 2015 Annual Meeting of the German Gesellschaft für Arbeitswissenschaft, held at Karlsruhe Institute of Technology (KIT) from February 26-28. The meeting featured more than 160 presentations and 30 posters reflecting the diversity of subject matter in the field of human and industrial engineering.